Pendidikan Agama Islam Berbasis Literasi Digital - Afif Hidayat (edujavare, 2025)
The importance of digital literacy learning in Islamic religious education today is inseparable from the rapid development of technology and information that affects all aspects of human life today. This article aims to provide a description of the concept of digital literacy in Islamic religious education. Therefore, to meet the challenges of these changes, a learning system, especially Islamic religious education, is needed to be able to prepare students to have the competencies needed in the future and provide a comprehensive and universal understanding of Islam. One effort that must be made now is to maximize digital literacy in Islamic religious education. Literacy today is not only the ability to read and write but also how a student can understand digital information. Through digital literacy in Islamic religious education, it is hoped that students will more easily understand Islam comprehensively both as a discipline, Islam normatively and historically.